Brand Engagement as A Key Factor In The Success of MEME Marketing In Generation Z - Rodhiah Rodhiah; Derizka Inva Jaswita; Muhardi Muhardi; Dede R Oktini; Tasya Aspiranti (International Journal of Management Science and Application, 2026)
The development of digital technology and social media has driven significant changes in marketing strategies, especially in reaching Generation Z who have unique characteristics in consuming content. One of the fastest-growing strategies is meme marketing, which relies on humor, creativity, and cultural relevance. This study aims to analyze the role of brand involvement as a key factor in meme marketing success, as well as test the influence of customer attitudes and media distribution as supporting variables. The study used a quantitative approach with a survey method of 100 Generation Z respondents in Jakarta. The sampling technique used purposive sampling, with the criteria of active respondents using social media. Data were collected through a Likert scale-based questionnaire and analyzed using a multivariate statistical approach. The results showed that brand engagement had a positive and significant effect on the effectiveness of meme marketing, while customer attitudes and media distribution had no significant effect. These findings confirm that the success of meme marketing is determined more by emotional interaction and active consumer involvement than rational factors or distribution channels. This research contributes to the development of digital marketing literature as well as practical implications for companies in designing communication strategies that are more relevant to Generation Z.